Pemodelan Pengetahuan Graph Database Untuk Jejaring Penelitian Kesehatan di Indonesia - Sahria, Yoga; Fudholi, Dhomas Hatta (STMIK Budi Darma, 2020)
Health research is research approved in the medical field. Health research in Indonesia is increasingly being approved by researchers in Indonesia, therefore research is stored in repositories. Many health research journal repositories are available, but there is minimal research for analysis and modeling in the health research network in Indonesia. This research proposes a knowledge modeling with Neo4j graphic database to implement it. In this study, data obtained from the SINTA Journal with web scraping techniques. The purpose of this research is to produce network knowledge using CQL (Chyper Query Language) which is useful in the medical field. The results of this study are expected to be useful for the government, academics, researchers, or the public for health research network researchers in Indonesia. The results of research testing modeling of health research network knowledge using a graph database of 95.2% said very good